EFEKTIVITAS EKSTRAK KULIT JERUK NIPIS (Citrus Aurantifolia) TERHADAP DAYA PROTEKSI NYAMUK - Marjan Wahyuni; Ricky Adiwanto (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2019)
Dengue Hemorrhagic Fever (DHF) is an acute fever caused by the dengue virus that enters human blood circulation through mosquito bites from the genus Aedes. Until now there is no cure for dengue disease, so people often panic if contracting the dengue virus. Various methods are used to prevent transmission of the dengue virus, one of which is the use of plants as a natural mosquito repellent. Continuous use of chemicals, besides adversely affecting health, will also make mosquitoes resistant. Therefore, it is necessary to use various alternative anti-mosquito drugs from plant species, one of which is lime. Lime skin contains one of the mosquito repellent substances so that it is possible for the lime peel to be effective as a mosquito repellent. This study aims to determine whether the extract from lime peel is effective as a mosquito protection power. The research method used was Quasi Experiment with 4 treatment activities and 3 replications, namely A (0%), B (15%), C (30%) D (45%). The object in this study was the aedes aegipty mosquito. Reppelent is considered effective if the protection power is ≥ 90%. The results showed that lime peel extract at a concentration of 15%, had a protective ability of 60%. At a concentration of 30% lime peel extract has a protection power of 90%. The protection of lime peel extract is very effective at a concentration of 45%, because it has a protective ability of 98%. With a concentration of 98% lime peel extract can be said as a mosquito repellent. The greater the concentration of orange peel extract, the greater the protection power obtained.